Representasi Poligami Dalam Film “Bismillah Kunikahi Suamimu” - Ali Syahputra (Sekolah Tinggi Agama Islam Negeri Majene, 2024)
This paper examines the practice of polygamy represented in the film Bismillah Kunikahi Suamimu by Vyntiana Itari. This paper explores the phenomenon of polygamy in a film that raises the question of how polygamy is represented in the film Bismillah Kunikahi Suamimu. The issue of polygamy in a film is very interesting to study to see if a film can provide education to the public. Through this film, people will easily gain knowledge, even though they are just watching, but without realizing they will gain knowledge. This research uses a qualitative approach by using Sara Mills' discourse analysis, the researcher's subjective interpretation is based on the representation theory developed by Stuart Hall. This paper focuses on the perspective of feminism and analyzes the position of the subject-object and the audience in representing polygamy in the film